The Position of Land Ownership Certificates in Settlement of Inheritance Disputes - Haras, Suryanto Jaya Putra; Marwan, Marwan; B, Sumiyati (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Land is one of the basic human needs. This article is motivated by the lack of legal certainty regarding land ownership. Many land disputes continue to arise due to inappropriate locations or boundaries, such as duplicate certificates. A certificate of ownership is a copy of the land register and its dimensions, if accompanied by a cover paper, the form of which is determined by ministerial regulations. The aim of this research is to understand certificates as proof of rights and title to land. The method used in this research uses a normative method, by analyzing existing legislation and literature. Based on the large number of cases related to land, it can be concluded that ownership of a land certificate is an important basic proof of land ownership. Ownership rights to land remain with the owner as long as the owner does not release or surrender his rights